The development of stereotactic body radiotherapy in the past decade: a global perspective. (October 2015) - Lo, Simon S; Slotman, Ben J; Lock, Michael; Nagata, Yasushi; Guckenberger, Matthias; Siva, Shankar; Foote, Matthew; Tan, Daniel; Teh, Bin S; Mayr, Nina A; Chang, Eric L; Timmerman, Robert D; et al.
In the past 10 years, there has been an exponential increase in the incorporation of stereotactic body radiotherapy, also known as stereotactic ablative radiotherapy, into the armamentarium against various types of cancer in different settings worldwide. In this article in the 10th year anniversary issue of Future Oncology, representatives from the USA, Canada, Japan, Germany, The Netherlands, Australia and Singapore will provide individual perspectives of the development of stereotactic body radiotherapy in their respective countries.